The new enhancement of OLSR energy-saving system in adhoc network - Suhazlan Suhaimi (2018)
In Mobile Ad Hoc Networks (MANETs), network nodes typically have short lifespansgiven that they are mobile, self-reconfigurable, and dependent on the battery power. Tohelp mitigate such a problem, the Optimize Link State Routing protocol (OLSR) isconsidered the most appropriate routing protocol to extend nodes' lifespans. As such,this study was undertaken with the main aim to enhance the energy-saving system ofMANET, with which nodes can function without failure by using a newly developedalgorithm of the OLSR protocol. Specifically, the study involved the developments ofthree schemes, namely a new Load Balance Energy Distributed (LBED) scheme, a newenhancement energy-saving (NEES) scheme, and a New Enhanced OLSR WillingnessCalculation (NEWC) scheme. Accordingly, a series of simulations was carried out tomeasure and quantify the performances of the LBED, NEES and NEWC schemes usingthe OLSR protocol. The performance criteria were based on the level of remainingbattery power (measured in percentage points), energy consumption, and number oflivenodes based on high data transmission rate and high mobility speed requirements. Thesimulations performed yielded several promising, interesting results. The new enhancedenergy-saving system was able to improve the battery power consumption significantlyby as much as 20%. Most promising, the mean percentage of network improvementusing the new enhancement energy-saving system was 48.18%, which was significantlyhigh compared to that of existing OSLR protocol. Such findings suggest that the newenhancement energy-saving system will be able to further improve the performance ofMANETs by making such networks more stable and reliable. In addition, the newenhancement energy-saving system was applied to a number ofnetwork scenarios basedon high mobility speed and high data transmission rate, the findings of which helpedformulate a solution matrix. This matrix can serve as a network configuration tool tohelp guide practitioners (especially network administrators) in setting up appropriatemobile networks that are badly needed to establish communication in critical situationsinvolving highly mobile nodes. Overall, the research findings suggest that the proposednew enhancement energy-saving system of the OLSR protocol can help improve theuse of battery energy in MANETs through efficient distribution of energy to networknodes. Effectively, such energy-efficient distribution can help prolong the life of eachnode, directly improve the selection of nodes as MPR nodes, provide more alternativeroutes in the network, and evenly distribute data transmission tasks to all nodes.Furthermore, the findings underscore the importance of selecting appropriate levels ofcritical parameters (e.g., the number ofnodes, size ofthe network space, mobility speed,and data transmission rate) that collectively will have a huge impact on the mobilenetwork performance. In this regard, practitioners can refer to the solution matrix toselect the most appropriate levels of such parameters that can help optimize the energyconsumption of the battery, thus leading to a stable, reliable mobile network.